The Effect of Using Earmuffs on Hearing Loss Complaints and Subjective Stress: A Quasi-Experimental Study among Weaving Workers in Surakarta, Indonesia - Setyawan, Haris; Qadrijati, Isna; Fajariani, Ratna; Rahma, Ratih Andika Akbar; Prasetya, Tofan Agung Eka (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Noise pollution from machine operations is one of industry's long-standing issues, especially in the textile manufacturing industry. High noise levels produced by weaving machine operation can harm employees' health, most notably hearing loss and stress at work. Since 1975, IT Co. Ltd., one of the biggest textile corporations in Surakarta, Indonesia, has struggled to find a solution to the issue of excessive noise, particularly in the weaving manufacturing facility. This study aims to determine the effect of employing earmuffs as a type of intervention to alleviate hearing loss complaints and subjective stress on weaving workers who are exposed to high-intensity noise. Methods: A time series design was used in this quasi-experimental study. This study’s participants were divided into 2 groups. The first group was weaving workers who used earmuffs as ear protection (Intervention Group), and the second group did not use earmuffs (Control Group). Data collection was carried out for 6 working days to see whether there was a significant effect of using earmuffs on hearing loss complaints and subjective stress. Results: From the second to the sixth day, using earmuffs as ear protection did not significantly reduce hearing loss complaints. However, it showed significant findings that increased the average score of subjective stress. Conclusion: Using earmuffs should protect the ears from noise exposure and its effects on workers' health. However, it has been shown that using earmuffs can increase the average score of hearing loss complaints and subjective stress.